On the economics of rational self-medication - Wisdom Akpalu (Fondazione Eni Enrico Mattei (FEEM), 2008)
It has been established in the medical literature that self-medicating with imperfect information about either the use of a genuine or counterfeit drug or based on wrong self-diagnosis of ailment, which is predominant especially in developing countries, is a risky investment in health capital. This paper models the decision to self-medicate and the demand for self-medicated drugs. We suppose that investment in self-medication depends on the perception of its effectiveness. The results obtained show that the decision to self-medicate depends on the relative price and perceived effectiveness of self-medication, the elasticity of the shadow value of health with respect to the quantity of health capital, and the relative effectiveness of self-medication in reducing the unpredictable changes in health capital. Furthermore, if an individual self-medicates, self-medication becomes a normal good: it increases if income increases; and it obeys the law of demand (i.e. it increases if its price, relative to that of the risk-free medication, decreases). Moreover, we have shown that some optimum subsidy can discourage self-medication.
Keywords: I12; I18; D81; C61; 330; Health Production; Self-Medication; Risky Investment; Government Policy; Dynamic Analysis; Krankheit; Rezeptfreies Arzneimittel; Entscheidung bei Unsicherheit; Mathematische Optimierung; Theorie